Is Complexity Science Embedded in Transformative Learning? - Ann L. Swartz; Karin Sprow (Adult Education Research Conference, 2010)
This paper discusses evidence that Jack Mezirow’s (1991) seminal work on transformative learning drew heavily from the precursors of complexity science without making the connection explicit, a trend still present in the transformative learning literature. The use of concepts from complexity theory and its interdisciplinary contributors can improve our understanding of transformative learning and its development.